Synovektomie der großen Gelenke in der Ära der Biologika - Carl, Hans-Dieter; Rech, Jürgen (Zeitschrift für Rheumatologie, 2011)
Since the mid 1980s, a global decrease in surgical procedures related to rheumatoid arthritis (RA) has been documented for joint-preserving procedures such as synovectomy as well as joint replacement surgery. This reflects improvements in the early management of rheumatoid arthritis and availability of more effective medical treatment. The present review summarizes the recent literature on the frequency of orthopaedic surgery in RA patients as well as the role of synovectomy in the rheumatoid hip, knee and shoulder in times of biological RA therapy. © 2011 Springer-Verlag.
CRIS-Team Scopus Importer:2021-02-03
Keywords: Biologicals; Joint; Rheumatoid arthritis; Surgery; Synovectomy